Enhancing the Competitiveness of MSMEs through Branding Optimization and Financial Reporting in Kembangan Selatan Subdistrict - Putri Dwi Wahyuni; Edy Suroso; Marsyaf Marsyaf (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This community service project aimed to address two critical challenges hindering the growth of Micro, Small, and Medium Enterprises (MSMEs) in Kembangan Selatan, Jakarta: weak branding and unstructured financial reporting. Through a structured program of training, workshops, and mentoring, we equipped 35 MSME owners with strategies for effective digital branding, including social media marketing and visual identity development. Concurrently, we provided practical training on preparing simple financial statements in accordance with the Indonesian Financial Accounting Standards for MSMEs (SAK EMKM), utilizing user-friendly digital tools. The program's effectiveness was evaluated through pre- and post-activity questionnaires, which showed a significant increase in participants' understanding, with average scores rising to between 3.23 and 3.63 on a 4-point scale. The initiative successfully produced multiple outputs, including video documentation, media publications, and intellectual property rights. Furthermore, it actively involved students, supporting the national